Effect of aripiprazole lauroxil on agitation and hostility in patients with schizophrenia. (March 2016) - Citrome, Leslie; Du, Yangchun; Risinger, Robert; Stankovic, Srdjan; Claxton, Amy; Zummo, Jacqueline; Bose, Anjana; Silverman, Bernard L.; Ehrich, Elliot W.
Abstract : This study aimed to evaluate the effects of aripiprazole lauroxil on hostility and aggressive behavior in patients with schizophrenia. Patients aged 18–70 years with a diagnosis of schizophrenia and currently experiencing an acute exacerbation or relapse were randomized to intramuscular (IM) aripiprazole lauroxil 441 mg ( n =207), 882 mg ( n =208), or placebo ( n =207) for 12 weeks. In post-hoc analyses, hostility and aggression were assessed by the Positive and Negative Syndrome Scale (PANSS) Hostility item (P7) and a specific antihostility effect was assessed by adjusting for positive symptoms of schizophrenia, somnolence, and akathisia. The PANSS excited component score [P4 (Excitement), P7 (Hostility), G4 (Tension), G8 (Uncooperativeness), and G14 (Poor impulse control)], and the Personal and Social Performance scale disturbing and aggressive behavior domain were also assessed. Of the 147 patients who received aripiprazole lauroxil 882 mg and with a baseline PANSS Hostility item P7 more than 1, there was a significant ( P <0.05) improvement versus placebo on the PANSS Hostility item P7 score by mixed-model repeated-measures at the end of the study, which remained significant when PANSS-positive symptoms and somnolence or akathisia were included as additional covariates. The proportion with PANSS Hostility item P7 more than 1 at endpoint was significantly ( P <0.05) lower with aripiprazole lauroxil versus placebo (53.6, 46.1, and 66.3% for 441, 882 mg, and placebo). A significant ( P <0.05) improvement was found with aripiprazole lauroxil versus placebo for change from baseline in the PANSS excited component score. The proportion of patients with aggressive behavior on the Personal and Social Performance scale was significantly ( P <0.05) lower for aripiprazole lauroxil: 30.0% for 441 mg versus 44.1% for placebo ( P =0.006) and 22.2% for 881 mg ( P <0.001 versus placebo). Treatment with aripiprazole lauroxil resulted in decreases in agitation and hostility in patients with schizophrenia and this antihostility effect appears to be independent of a general antipsychotic effect.